Bullying: Detection Through the Sociometric Test and Prevention Through the Experiences Based on the Socioaffective Method - Hamodi-Galán, Carolina (2019)
Nowadays, bullying is one of the most common forms of violence at school. This article includes an experience in which sociometry is used as a methodology implemented to know the current relationships between students in the class (through a sociometric test and a sociometric matrix), along with qualitative research tools (field diary and observation guide), in order to develop a mixed methodology (a quantitative and qualitative research design). The results obtained outline the importance of implementing, in class, dynamics that work on empathy and social abilities and the resulting positive impact on the class.